Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1371/journal.pone.0042160
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Early Surface-Associated Growth of Shewanella oneidensis MR-1

Abstract: Bacterial biofilm formation starts with single cells attaching to a surface, however, little is known about the initial attachment steps and the adaptation to the surface-associated life style. Here, we describe a hydrodynamic system that allows easy harvest of cells at very early biofilm stages. Using the metal ion-reducing gammaproteobacterium Shewanella oneidensis MR-1 as a model organism, we analyzed the transcriptional changes occurring during surface-associated growth between 15 and 60 minutes after atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 79 publications
(80 reference statements)
0
20
0
Order By: Relevance
“…In a previous study, we demonstrated that early surface-associated growth induces the expression of genes belonging to the putative OxyR (oxidative stress defense regulator) and Fur (ferric uptake regulator) regulons in S. oneidensis MR-1 (48). Based on these and ⌬recA deletion mutants (recA Ϫ) after UV exposure (ϩ) or without UV exposure (Ϫ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we demonstrated that early surface-associated growth induces the expression of genes belonging to the putative OxyR (oxidative stress defense regulator) and Fur (ferric uptake regulator) regulons in S. oneidensis MR-1 (48). Based on these and ⌬recA deletion mutants (recA Ϫ) after UV exposure (ϩ) or without UV exposure (Ϫ).…”
Section: Resultsmentioning
confidence: 99%
“…If required, FeCl 2 or desferrioxamine mesylate salt was added to the medium reservoir. For protein sampling, biofilm cells were cultivated in 50-ml syringes on glass beads under constant medium flow and harvested as described earlier (48).…”
Section: Methodsmentioning
confidence: 99%
“…It is likely that the physiological response is an energetically costly process, requiring complex regulatory changes. For example, the response leading to S. oneidensis biofilm formation depends on the coordinated expression of multiple multisubunit structures, such as pili and adhesins, as well as large shifts in metabolism (46). Similar complex levels of regulation are probably necessary to control the extension of the outer membrane in the form of nanowires.…”
Section: Differentially Expressed Genes During Electron Acceptor Limimentioning
confidence: 99%
“…Recently, G€ odeke et al 11 investigated the bacterial surface-associated growth in a flow chamber. They revealed several transcriptional changes during the earlier stage of cells surface colonization, and especially the expression changes in functional genes coding for transport and conversion of carbohydrates, amino-acid transport and metabolism, lipid metabolism, gluconate catabolism, and also phage genes regulation.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, few studies have been indeed performed to investigate specifically the early stage of growth of initially adhering bacteria or cells on solid surfaces [9][10][11] in terms of growth kinetics and its coupling with the local hydrodynamics.…”
Section: Introductionmentioning
confidence: 99%